PSYCHOLOGICAL ASPECTS OF SOCIAL ADAPTACION OF WOMEN CANCER PACIENTS - Iryna Viktorivna Serhet (Insight: the psychological dimensions of society, 2019)
The article explores the aspects of social adaptation of women patients with confirmed oncologic disease, social and psychological peculiarities of them. Purpose of the research is theoretical and empirical investigation of psychological aspects of social adaptation of women with cancer.Methods of research. The following methods have been used in order to solve the research tasks: theoretical methodological analysis, systematization and generalization of data for the research problem The empirical methods of research have been chosen the “Methodology for the study of personal identity” and “Methodology for the study of professional identity” by L. B. Shneider, “Loneliness scale” by Russell, D, Peplau, L. A. & Ferguson, M. L. Statistical methods: methods of mathematical statistics, comparative analysis, Pearson linear correlation coefficient. Two groups of women have been participated in the research. Sample amounted 40 people. The first group consisted of the women who work in “Kherson regional oncological dispensary”, the second group consisted of patients of Gynecology and Radiology departments of the same hospital who are on inpatient and outpatient treatment during six months for the gynecological localization. The patients underwent surgical treatment. None of the subjects were in terminal state and according to medical opinion their disease had positive prognosis. The results of research. Based on the results of the research it has been established that when the person has oncologic disease both the biological aspect of life and social context of existence are disturbed. Data received shows that there is the specific nature of psychological aspects of social adaptation for women with oncology. This date give the opportunity to find out the way of psychological help for this category of patients with the focus on rethinking life situation, correction of interaction systems, expanding the prospects of the future. Conclusion. Based on the received results of the research we see that even on the initial stages of the disease there are changes in the interpersonal relations and accepting the role of patient, which decreases life understanding, gives the negative color to the life situation, narrows time perspectives, and changes the life strategy in the whole. There is the reinterpretation of personal life which becomes the stage of acquiring of new identity.